THE EFFECTS OF CARDIAC REHABILITATION ON HYPERTENSIVE BURDEN AND ARTERIAL STIFFNESS IN HYPERTENSIVE PATIENTS. A RANDOMIZED CROSSOVER STUDY. (April 2021) - Kallistratos, Manolis; Tsinivizov, Pavlos; Poulimenos, Leonidas; Latsou, Dimitra; Andriopoulou, Maria; Dimaki, Niki; Kouremenos, Nikos; Koukouzeli, Aggeliki; Pittaras, Andreas; Kyfnidis, Kostas; Triantafyllis, Andreas; Varvarousis, Dimitris; et al.
Abstract : Objective: To investigate the effect of continuous versus intermittent exercise on hypertensive burden as well as the correlation of pulse wave velocity (PWV) with various parameters of CPX testing. Design and method: A randomized crossover study that will enroll 150 hypertensive patients. Patients will be randomized on continuous or intermittent exercise program for three months, then will follow a month of wash out period and the patients will be cross over from continuous to intermittent and vice versa for another three months of exercise. In all subjects, routine blood chemistry, including SUA determination, echocardiographic examination, office and 24 h ambulatory blood pressure (BP) as well as 24 h ambulatory PWV and central (BP) measurement as well as CPX testing will be performed in all study stages. Results: We present the preliminary results of 32 hypertensive patients (mean age 65.1 ± 11.3 years). A negative correlation was found between PWV and Peak VO2 (r = -0.540, p = 0.002), (r = -0.508, p = 0.045) at baseline and after 3 months of exercise. Peak VO2 was inversely correlated with PWV (r = -0.512, p = 0.003) and positive with diastolic BP (r = 0.469, p = 0.008), but not with systolic BP levels (p = ns). Eighteen patients until now have completed the 3 months of exercise. PWV, systolic and diastolic BP levels were decreased while Peak VO2 levels were increased between baseline and after 3 months of exercise but with no statistically significant differences. Specifically, the mean baseline PWV was 9.26 (±1.60) m/sec and the final PWV was 9.23 (±1.60) m/sec (p = 0.769). The mean of systolic and diastolic BP 127.59 (±7.94)/ 78.12 (±8.57) and 124.59 (±7.57)/ 77.24 (±8.57) mmHg for baseline and after three months of exercise (p = ns). The mean of Peak VO2 levels were 21.63 (±4.61) and 22.24 (±3.97) ml/kg/min for baseline and after three months of exercise (p = 0.394). It has to be mentioned however that in 6 patients (33%) the antihypertensive drug regiment was reduced. Conclusions: PWV was significantly correlated with functional capacity levels irrespectively of the levels of systolic BP. Cardiac rehabilitation may decrease BP levels or the number of antihypertensive drugs.